Pendamping Koperasi Modern Di Dinas Koperasi dan UMKM Daerah Istimewa Yogyakarta - Ambar Kinanthi (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2023)
MSIB is part of the Kampus Merdeka program which aims to provide opportunities for students to learn and develop themselves through activities outside the lecture classroom. There are many partners who participate and contribute in honing student knowledge, one of which is the Cooperative and Small and Medium Enterprises Office of the Special Region of Yogyakarta or commonly known as DIY UKM DISCOP. DIY Cooperative and SME Office Certified is an activity designed to solve problems in Cooperative and SME Assistance in the 2023 Modern Cooperative Pilot. It is expected that after participating in this program, participants will master how to identify a cooperative in order to better utilize the presentation of data. Students who graduate in this program are expected to be able to also compile plans in business development in a company.